PELAKSANAAN ITSBAT NIKAH DI PENGADILAN AGAMA PADANG KELAS 1 A - Irma Irawati dan Joni Zulhendra (Normative Jurnal Ilmiah Hukum, 2019)
The family is one of the smallest social units in society, the formation of a family is the existence of a strict bond between a woman and a man that is carried out in marriage. "Article 1 of Law Number 1 of 1974 concerning marriage is an inner and physical bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the Godhead of the Almighty. Marriage not only unites two human couples, namely male and female, but ties the sacred covenant in the name of God. Marriage does not only rely on the teachings of God in the Koran and As-Asunnah, but the marriage is declared valid if according to the law of God and state law has fulfilled the pillars and conditions. The result of the research is that marriage is submitted due to the absence of authentic evidence of a marriage, while the intended evidence is a marriage certificate, due to the loss or marriage outside the control of the marriage registrar, so the marriage is not registered and does not have authentic evidence or at the time of now known as marriage under the hand. The obstacle faced in the implementation of itsbat marriage in the Padang Religious Court is that the petitioners had difficulty in presenting witnesses and transportation costs, the court found it difficult to prove whether the marriage was valid or not. The solution is that the marriage must be in accordance with the rules of the Islamic religion and take place before the marriage registration employee according to article 2 paragraph 2 Law No. 1 of 1974: marriage is legal if it is carried out according to the laws of each religion and belief, each marriage is recorded according to applicable laws and regulations.